Still more tell me why; answers to hundreds of questions children ask. - Leokum, Arkady; Koehler, Cynthia Iliff; Koehler, Alvin (New York, Reed Childrens, 2000)
Over 472 answers to commonly asked questions such as "Why is sugar sweet?" and "Did dragons really live?"
Keywords: Children's questions and answers; Questions and answers